Implementation of the European Union´s packaging and packaging waste regulation: A decision support framework combining quantitative environmental sustainability assessment methods and socio-technical approaches - Niero, Monia (Cleaner Waste Systems, 2023)
The recent proposal for a European Union Regulation on packaging and packaging waste has a two-fold aims: i) to reduce the negative environmental impacts of packaging and packaging waste and ii) to improve the functioning of the internal market. Life Cycle Assessment (LCA) has historically been able to address the specific objectives of the proposal and is recognized as a key decision support tool in the circular economy context. In this short communication, it is argued that the new EU regulation calls for systemic changes, i.e. changes that are not simply just technological changes, but changes that might give rise to conflicts among actors and that are reliant on the active involvement of end-users. Therefore, to tackle the challenges in the implementation of the requirements of the new regulation a multi-disciplinary research approach able to address both technical aspects and social relations is needed. Accordingly, a conceptual framework combining quantitative environmental sustainability assessment tools (i.e. LCA and Material Flow Analysis) and qualitative socio-technical approaches (i.e. Actor-Network mapping and Practice Theory) is presented. The added value of such combination is illustrated in relation to two cases relevant for packaging, i.e. take-away food and food waste sorting. To exploit the full potential of LCA as a support to the decision-making process, the need to move beyond a product-centric analysis and instead adopt a socio-material perspective is outlined and the packaging sector has the potential to be a frontrunner in this context. •New EU legislative proposal on packaging waste focuses on promoting waste prevention and reuse.•Life Cycle Assessment (LCA) can support decision making process but ignores social relations.•Material Flow Analysis (MFA) allows mapping of physical (i.e. non-human) flows but lacks human actors.•Actor-Network (AN) mapping and Practice Theory (PT) are enablers for understanding how things work.•A conceptual framework combining LCA, MFA, AN and PT is outlined for life cycle management.